The association of Aedes aegypti and Ae. albopictus in Allende, Nuevo León, Mexico. - Mercado Hernández, Roberto; Aguilar Gueta, Juan de Dios; Fernández Salas, Ildefonso; Earl, Paul R. (American Mosquito Control Association, 2006)
The recent appearance of Aedes Stegomyia albopictus (Skuse) in Nuevo León (NL) worries health officials. It is a vector of dengue fever in Asia and is more resistant to lower temperatures than Ae. aegypti. The objective of this study was to learn about some ecological parameters of Ae. albopictus and their association with Ae. aegypti, and other culicids in Allende, NL, Mexico, during 1999. Allende is a small town close to metropolitan Monterrey, which has 4 million inhabitants. The design was random with monthly sampling of 175 ovitraps. Chi-square analyses were performed with data of presence, absence, frequency, and relative abundances. During the study, the species Culex tarsalis (Coquillet), Cx. thriambus (Dyar), Cx. pipiens (Linnaeus), Cx. coronator (Dyar and Knab), Ae. albopictus, Ae. aegypti, Toxorhynchites rutilus (Coquillet), and Ae. triseriatus (Say) were found. April is the month for large numbers of mosquito species. September had the highest populations in positive ovitraps (66.67%), followed by July (63.27% of traps). Aedes aegypti was the most abundant (65.13%), followed by Ae. albopictus (19.71%). Both Ae. albopictus and Ae. aegypti were found from April until December. Aedes aegypti was more abundant than Ae. albopictus, except in August, when they were similar (χ2 = 0.197, P < 0.05). We found significant association between the presence of both species for every study month (χ2 = 9.837, P < 0.05), with a contingency coefficient of 0.247. September and November were the months having the most mosquitoes in this association. Only considering Ae. albopictus, more were found in ovitraps in July (34.6%), followed by September (33.3%). However, its presence was not significant throughout the year. Of 2 zones, in town and at the river, prevalence indicated that Ae. albopictus preferred the river. This mosquito is in its establishment phase in this area and requires further studies.